2014
DOI: 10.1002/polb.23447
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐hexylthiophene) aggregate formation in binary solvent mixtures: An excitonic coupling analysis

Abstract: The aggregation behavior of P3HT [Mn ≈ 28.2 kDa, regioregularity >96%, PDI ≈ 1.3] in 96 solvent mixtures is studied using UV–vis absorption spectroscopy. Hansen solubility parameters and Spano excitonic coupling analyses are used to identify correlations between the properties of the solvent mixtures and the extent of structural order of the aggregates. It is clear that the identity of the poor solvent used to drive aggregation has a significant impact on the excitonic coupling behavior and, hence, the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 49 publications
9
58
0
Order By: Relevance
“…The question is the kinetics of the process. In recent papers, time dependences of coil-to-rod transitions (authors followed changes within tens of minutes) [33] are reported as well as coil-to-rod transition and p-p stacking in the polythiophene derivatives with alkyl side chains [34]. We observe much slower relaxations in comparison to the poly(3-alkylthiophene)s which is very probably result of stronger intermolecular interactions in our system.…”
Section: Time Evolutionmentioning
confidence: 63%
See 1 more Smart Citation
“…The question is the kinetics of the process. In recent papers, time dependences of coil-to-rod transitions (authors followed changes within tens of minutes) [33] are reported as well as coil-to-rod transition and p-p stacking in the polythiophene derivatives with alkyl side chains [34]. We observe much slower relaxations in comparison to the poly(3-alkylthiophene)s which is very probably result of stronger intermolecular interactions in our system.…”
Section: Time Evolutionmentioning
confidence: 63%
“…In addition, we performed experiments illustrating the association behavior: dynamic light scattering, atomic force microscopy and transition electron microscopy. We also report on the time-dependent processes in solutions as the dynamics of de-association processes are reported only rarely [33,34].…”
Section: Introductionmentioning
confidence: 98%
“…A mixture of chloroform and acetonitrile (4:1, v/v) was used for coassembly of the P3HT and QDs. [ 59 ] Using the solution-biphase method, micrometer-long NWs branched off in all directions from the central aggregates ( Figure 5 a and S20a-c, Supporting Information). However, the one-pot addition method generated star-shaped nanostructures with short multiarms (Figure 5 b).…”
Section: Self-assembly Behaviors Of P3ht Depending On the Solvent MIXmentioning
confidence: 98%
“…Johns et al determined that, to start the formation of stable nanowire, at least about 60 monomers should exist within the interacting chain segment of the polymer aggregates. Interaction of polymer chains consisting of less than 60 monomers, causes the breaking of the bonds between the polymers due to thermal motion, and polymers become independent from each other [8]. If the required critical mass is provided, then aggregation begins and polymers bind along the π-π stacking direction in microseconds forming stable-core wires [6].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of solution phase self-assembly is explained in terms of polymer interactions [4,[6][7][8]. When poor solvent is added to polymer solution, P3HT polymers tend to minimize the unfavorable contacts between backbone and hydrocarbon solvent due to the solvophobic interactions which results in polymer chains getting closer and increasing the chain-chain interaction [9].…”
Section: Introductionmentioning
confidence: 99%